Guttate Psoriasis that Evolves to Chronic Plaque Psoriasis induced by Atypical Bacterial Infection - Jesryn Dhillon; Cut Putri Hazlianda (Indonesian Journal of Global Health Research, 2025)
Guttate psoriasis is the second most common variant of psoriasis found in children and young adults. It is known that several factors such as infections, alcohol consumption, drugs, trauma, acute discontinuation of potent topical or systemic corticosteroids, body mass index, and endocrine disorders are known to be associated with the occurrence and development of guttate tu. This study aims to report a case of varicella with bronchopneumonia in an adult patient. Data were collected through anamnesis, physical examination, laboratory and microbiological investigations, and follow-up assessments, then analyzed qualitatively and presented descriptively as a case report. A 27-year-old man came to our polyclinic with multiple erythematous papules and multiple plaques, milliar-lenticular-nummular in size, discrete, accompanied by the white scale on the scalp, thoracic, vertebral, axillary, right, and left brachial and lower extremities. Two throat swab examinations showed different bacterias and were later found to be induced by periodontitis. This patient was then treated for chronic plaque psoriasis with methotrexate and showed good progress.